Natural deep eutectic systems as alternative nontoxic cryoprotective agents - Castro, Vânia I. B. (2019)
The research leading to these results has received funding provided by Portuguese Foundation for Science and Technology (FCT), through project PTDC/BBB-EBB/1676/2014 - DesZyme. Funding from the European Union Horizon 2020 program has also been, granted through the project Des.solve (ERC consolidator), ERC-2016-COG 725034. J.M.S. would also like to acknowledge the financial support by the FCT through the post-doctoral grant with reference number SFRH/BPD/116779/2016.